PERAN BPSDMD PROVINSI NTB DALAM MENGEMBANGKAN BALE MEDIASI SEBAGAI WADAH PENYELESAIAN KONFLIK SOSIAL YANG PROFESIONAL DI PROVINSI NTB - Syafi’i Syafi’i (Sekolah Tinggi Pariwisata Mataram, 2022)
This research aims to determine the urgency of the presence of the Bale Mediation Institution in resolving social conflicts in West Nusa Tenggara Province, the second is to analyze the efforts that BPSDMD NTB can take in developing the competence of Bale Mediation mediators in order to create a professional social conflict resolution forum in NTB Province in order to overcome the lack of certified mediator at Bale Mediation. The research method used is a qualitative method with data collection techniques used, namely field studies and library studies. The result of the research is that Bale Mediation is very important and needed by the community in helping to resolve social conflicts that occur both criminal and civil disputes because the principles used in dispute resolution are based on local wisdom and also problem solving in Bale Mediation is carried out in a peaceful manner so that there is no parties who feel disadvantaged (win-win solution) and speed up the dispute resolution process. However, mediation Bale still has a weakness, namely the limited number of certified mediators. BPSDMD NTB Province is an institution that has the authority, duties and functions in overcoming the problems faced by the mediation committee with the efforts that can be done, namely conducting training or certification of mediators.